Species-specific resource availability as potential correlates of foraging strategy in Atlantic Forest edge-living common marmosets. Issue 4 (4th July 2022) - Souza-Alves, João P.; Chagas Alves, Renata R.D.; Hilário, Renato R.; Barnett, Adrian A.; Bezerra, Bruna M.
Abstract : In seasonal environments, while some primates change their behavioural patterns according to the total food available, others associate it with plant-specific food availability. We recorded behavioural and ecological data from one marmoset group at the edge of a 522-ha Atlantic Forest fragment in order to verify the seasonal and between-year patterns. We collected behavioural and diet data via scan sampling for 9 months (3 months/season), and estimated the fruiting source density. Fruit resources were significantly more available in the 2012 dry season than the 2012 rainy and 2013 dry seasons. Overall, foraging and moving were the main activities, and fruits and exudates were the principal food items consumed. During the rainy season, the common marmosets devoted more time to eating fruits, increased the niche breadth and food source revisitation frequency, and used the forest's middle-strata more often. When we compared between-year data, we found that common marmosets rested more frequently, fed more often on invertebrates and had a broader niche breadth in the 2012 dry season than in the 2013 dry season. The availability of specific fruit resources and invertebrates appeared to influence study group activity budget and diet. Variation in food availability may have reduced diet niche breadth and stratum use. Our study confirms the well-established flexibility of common marmosets, and demonstrates key aspects of their foraging strategy to survive in modified habitats.